Efektivitas Pengukuran Kinerja Keuangan Terhadap Harga Saham Pada Perusahaan Pertambangan Sub Sektor Batu Bara Yang Terdaftar Di Indonesia Stock Exchange - Maria Reineldis Jemimi; Ratih Dewi Titisari Haryana (CV. Ulil Albab Corp, 2024)
This research aims to determine the effect of stock ratio, return on assets and return on equity on share prices in coal sub-sector mining companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The companies in the sample are 11 of the 25 coal sub-sector mining companies listed on the Indonesian Stock Exchange from 2019 to 2022. The data collection technique used is documentation. Meanwhile, the data analysis used is statistical techniques using the SPSS version 23 program. The analytical method used is multiple linear analysis. Before carrying out the test on multiple linear equations, classical assumption testing consisting of data normality test, multicollinearity test, heredity test and autocorrelation test. After the data is free from classical assumptions, hypothesis testing is carried out using the t test to see the influence of each independent variable on the dependent variable. Based on the results of the analysis, it is known that the current ratio, return on assets and return on equity variables have a significant effect on stock prices.